Numerical simulation and experimental analysis on the deformation and residual stress in trailing ultrasonic vibration assisted laser welding. (October 2022) - Liu, Zuguo; Jin, Xiangzhong; Li, Junhao; Hao, Zhongjia; Zhang, Junyi
Highlights: A new welding technology is proposed, which introduces the trailing ultrasonic vibration into the conventional laser welding process. Trailing ultrasonic assisted laser welding (T-ULW) on grain refinement and mechanical properties of weld was studied. In the finite element simulation analysis of T-ULW, a novel heat source model fitting the actual weld is proposed. Sequential coupled finite element simulation and experiment reveals the accuracy and efficiency of the proposed approach. Abstract: A trailing ultrasonic-assisted laser welding (T-ULW) technology is first proposed to weld SUS301 stainless steel sheet with a thickness of 0.6 mm. Secondly, welding experiments with conventional laser welding and ultrasonic-assisted laser welding are carried out on SUS301 stainless steel thin sheet, and the weld morphologies are obtained. Thirdly, based the experimentally obtained cross section shape of the weld, a novel heat source model is proposed by means of polynomial fitting the actual weld contour. Fourthly, the welding temperature field, the welding deformation and residual stress are simulated, and the welding temperatures at some special points in the sample, the welding deformation and residual stress are measured. These experimental measurement results agree very well with the corresponding simulation results, which verify the proposed analysis approach based on the above novel heat source model is feasible and has high enough accuracy. Finally, the mechanism of how ultrasonic vibration affects the stress distribution in the samples welded by ultrasonic-assisted laser welding is discussed. Ultrasonic vibration affects the residual stress distribution of the weld mainly through two mechanisms. One is that ultrasonic vibration can speed up the flow of the molten material in the molten pool, and then make the temperature distribution there more uniformly and decrease the temperature gradient, and finally decrease the residual stress of the weld. The other one is that ultrasonic vibration can result in compression and plastic deformation, which finally increase to some extent the compressive stress of the weld near the ultrasonic vibration exerted.